2023
DOI: 10.1038/s10038-023-01163-z
|View full text |Cite|
|
Sign up to set email alerts
|

Is legislation to prevent genetic discrimination necessary in Japan? An overview of the current policies and public attitudes

Abstract: Genetic discrimination (GD) has not been discussed in East Asia as extensively as in Europe and North America. Influenced by UNESCO’s universal declaration in 1997, the Japanese government took a stringent approach toward GD by releasing the Basic Principles on Human Genome Research in 2000. However, Japanese society has mostly been ignoring the prevention of GD for decades, and the principle of prohibiting GD was never adhered to in any of the Japanese laws. We conducted anonymous surveys among the general ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Six of the eight surveys included a certain aspect of GF ( Middleton et al, 2020 ) and GL as components of awareness ( Ikeda, 2008 ; Ishiyama et al, 2008 ; Hishiyama et al, 2019 ; Ri et al, 2022 ; Muto et al, 2023 ). Regarding GF, Middleton et al (2020) reported that 88% of Japanese respondents answered not familiar with DNA, genetics, or genomics .…”
Section: Awareness Attitude and Intentionmentioning
confidence: 99%
See 4 more Smart Citations
“…Six of the eight surveys included a certain aspect of GF ( Middleton et al, 2020 ) and GL as components of awareness ( Ikeda, 2008 ; Ishiyama et al, 2008 ; Hishiyama et al, 2019 ; Ri et al, 2022 ; Muto et al, 2023 ). Regarding GF, Middleton et al (2020) reported that 88% of Japanese respondents answered not familiar with DNA, genetics, or genomics .…”
Section: Awareness Attitude and Intentionmentioning
confidence: 99%
“…Three of the eight surveys ( Ikeda, 2008 ; Hishiyama et al, 2019 ; Muto et al, 2023 ) touched on aspects of the rules of GR—namely, the existence of regulations, recognition of the content of the regulations, and perceptions of genomic information in the regulations.…”
Section: Awareness Attitude and Intentionmentioning
confidence: 99%
See 3 more Smart Citations